"Money can't buy me land": Foreign land ownership regime and public opinion in a transition society. (September 2016) - Gugushvili, Alexi
Highlights: The question of foreign ownership of agricultural land in transition societies has attracted considerable political, social and media attention. Georgia first established and then started to repeal its free foreign land ownership regime. About three-quarters of residents are against the sale of land to foreign citizens, the second highest rate among 32 countries with comparable data. History, economic protectionism, xenophobia and ethnic national identity are the main explanations of individuals' negative attitudes. Abstract: In recent years, as part of the broader policies of economic liberalization, the sale of agricultural land to foreign citizens has attracted considerable political, social and media attention in transition societies. The regime of land ownership in Georgia has evolved from the complete restriction of foreign acquisition in the beginning of the 1990s, to the unrestricted sale of land to foreign citizens from 2010 onwards. An analysis of newly-available data from International Social Survey Programme's (ISSP) National Identity module suggests that respondents in Georgia, along with Russia, hold the most negative attitudes toward selling land to foreigners compared to other countries. I hypothesize that this is the result of a confluence of factors such as the communist legacy, historical memory, rural nationalism, agricultural underdevelopment and inequality. The quantitative part of this article tests socio-demographic, geographic, ideological, and identity-based explanations of within-country variation in attitudes toward the purchase of land by foreigners. The results suggest that socio-demographic and geographic variables such as respondents' age and regional belonging explain some variance in the dependent variable, but that the major effects stem from individuals' perceptions of economic protectionism, xenophobia, and ethnic national identity.